PENGARUH PEMBERIAN EDUKASI DENGAN MEDIA VIDEO TERHADAP TINGKAT PENGETAHUAN MASYARAKAT KUIN CERUCUK BANJARMASIN DALAM MENGELOLA OBAT RUSAK DAN KEDALUWARSA - Mahrita, Mahrita; Saputera, Mochammad Maulidie Alfiannor; Kurniawan, Guntur (Jurnal Insan Farmasi Indonesia, 2023)
In daily life, people use and store medicines at home for self-medication. Medicines that are stored and not used properly can cause drug damage and drugs to accumulate until the expiration date. The purpose this study was to determine the effect of providing education with video media on knowledge in managing damaged and expired drugs in the Kuin Cerucuk Banjarmasin Village community. This study used a pre-experimental research design with a One Group Pretest Posttest approach. The number of respondents this study were 100 respondents who met the inclusion and exclusion criteria. Data collection used a validated knowledge questionnaire and sampling was done door to door. The results study shows the level of knowledge before being given education with video media, namely the good category 9%, the sufficient category 46% and the less category 45%. While the level of knowledge after being given education with video media 80% good category, 20% sufficient category and 0% lacking category. Based on non-parametric tests using Wilcoxon test, it is known that the p value = 0.000 with a significance level <0.05, which means that there a significant (real) influence between the level of knowledge before and after being given education through video media.